Kajian Bahan Ajar Mata Kuliah Teori Mesin Listrik dan Relevansinya dengan Kurikulum 2009 - Ahmad Sujadi; Sunyoto Sunyoto (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectives of this study were: (1) to examine the relevance of the teaching materials applied in the subject of Electrical Machines Theories related to the 2009 curriculum syllabus; (2) to reorganize thematerials delivered to the students based on the time management. The approach utilized in this study was content analysis. In this study, the explicit description of the study process was crucial. To assess the teaching materials that had been arranged and would be rearranged based on the time management the data resulted from documentation, observation, and interviews was required. It was carried out to complete the data for the handbook of Electrical Engineering Theories. The results revealed that the materials in the handbook are mostly relevant to the 2009 curriculum, but the time management needs to be reviewed. Theeliminated materials will be included in independent assignments or other relevant subjects.